Values And Globalization: Issues In Preserving National Heritage - Djaxongir Bayaliyev; Umarov Muhammadjon (Periodica Journal, 2025)
The article analyzes the preservation and development of national values in the process of globalization. It highlights the importance of protecting cultural heritage, ensuring spiritual development, and educating the younger generation on the basis of national ideas
Keywords: values; globalization; national heritage